AHMADIYAH (Analisis Kritis Terhadap Teologi dan Pemikirannya) - Riski Ayu Amaliah; Muhammad Amri; Mahmuddin (Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this study is to discuss critical analysis of Ahmadiyya theology and thought using literature. The purpose of this writing is to find out about the history of the birth of Ahmadiyah, the life history of Mirza Gulam Ahmad, the understanding of Ahmadiyya which is considered controversial and the development of Ahmadiyya in Indonesia. The results of this paper show that Ahmadiyya emerged in the 19th century when Muslims were experiencing a setback. Ahmadiyah was founded by Mirza Gulam Ahmad who is considered a messenger of Allah SWT, and has even proclaimed himself the promised Messiah and al-Mahdi. Ahmadiyah is divided into two, namely Ahmadiyah Qadian and Ahmadiyah Lahore. Mirza Gulam Ahmad's thoughts are considered heretical by some people, because many of his thoughts are contrary to the values of Islamic teachings. The development of Ahmadiyya in Indonesia started with the establishment of Qadian schools for young people. In addition, its development is also through books and magazine publications originating from abroad.